New frontiers in sport training: Genetics and artistic gymnastics - Morucci, G.; Punzi, T.; Innocenti, G.; Gulisano, M.; Ceroti, M.; Pacini, S. (The Journal of Strength and Conditioning Research, 2014)
The increasing understanding of the genetic influences in sport has prompted an association study between the athletic performances and the polymorphisms of the angiotensin-converting enzyme (ACE), the a-actinin-3 (ACTN3), and the vitamin D receptor genes. The details of these gene polymorphisms can provide useful information to improve and plan new modern training programs for elite athletes. Eighty Italian male high level gymnasts were trained and tested for gymnastic-specific exercises and tested in all the men's artistic gymnastic apparatus (floor, pommel horse, rings, vault, parallel bars, and horizontal bar), and then genotyped. The training parameters of volume, intensity, and density of each gymnast were periodically measured during the season in each apparatus from the tests performed, and the seasonal average values were calculated. Gene polymorphisms were determined by polymerase chain reaction restriction fragment length polymorphism assay and studied in association with the performance results. The performances of ACE II gymnasts were significantly lower than that of the ACE ID/DD gymnasts in the apparatus expressing power features, confirming the predisposition of these athletes toward power-oriented sport. Gymnasts with ACTN3 RR/RX genotypes did not show a predisposition to the power-oriented apparatus, having worse performances compared with that of the ACTN3 XX gymnasts. Similarly, gymnasts with ACE II + ACTN3 RR/RX combined genotypes showed lower performances in comparison with that of the other gymnasts. Vitamin D receptor polymorphisms showed no significant association with the athletic performances. Because ACE insertion/deletion (I/D) and ACTN3 R577X polymorphisms heavily affect the physical performance of elite male gymnasts, the Italian Gymnastic Federation trainers have started to customize the current high-level training programs.